2018
DOI: 10.5961/jhes.2018.262
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views, experiences and suggestions with respect to academic honesty in higher education: a phenomenological study

Abstract: Çalışmanın amacı, üniversite öğrencilerinin akademik dürüstlükle ilgili görüşlerini ve deneyimlerini incelemektir. Çalışmanın amacına ulaşmak için, nitel araştırma desenlerinden birisi olan olgu bilim deseni kullanılmıştır. Çalışmanın örneklemini, maksimum çeşitlilik örneklemesi yöntemiyle çalışmaya dâhil edilen Ankara'daki bir yükseköğretim kurumunun farklı bölümlerinde öğrenim görmekte olan 18 lisans öğrencisi oluşturmaktadır. Araştırmacılar, öğrencilerle birebir görüşmeler gerçekleştirmek için yarı-yapıland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These findings underscore the significant role parental pressure can play in fostering academic dishonesty among students. Yıldırım and Orhan (2018) interviewed eighteen Turkish university students about academic dishonesty regulations. They found that students were neither informed of the regulations nor received training about what is considered academic dishonesty.…”
Section: Moral Disengagement and Academic Dishonestymentioning
confidence: 99%
“…These findings underscore the significant role parental pressure can play in fostering academic dishonesty among students. Yıldırım and Orhan (2018) interviewed eighteen Turkish university students about academic dishonesty regulations. They found that students were neither informed of the regulations nor received training about what is considered academic dishonesty.…”
Section: Moral Disengagement and Academic Dishonestymentioning
confidence: 99%